1999
DOI: 10.1002/(sici)1096-8628(19990625)89:2<58::aid-ajmg2>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Preconception care: Challenge of the new millennium?

Abstract: Couples who plan their pregnancies can elect anticipatory care with the aim of improved health for mother and child. While it has proved to be beneficial in such specific disorders as maternal diabetes mellitus, preconception care is not yet established as a part of primary care. Preconception care is a form of community genetics and consists of three main components: risk assessment, health promotion, and intervention. Intake of folic acid during the time surrounding conception is important in preventing neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A pilot preconception clinic in Maastricht was developed as a forum in which women planning a pregnancy could address questions and concerns. Couples attending the clinic responded favorably to the program and indicated that they would not have asked their general practitioner such questions [ 35 ]. These findings are supported by the results of recent surveys of Dutch women in which more than 70% of the respondents reported an interest in preconception counseling when offered by their own general practitioner [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A pilot preconception clinic in Maastricht was developed as a forum in which women planning a pregnancy could address questions and concerns. Couples attending the clinic responded favorably to the program and indicated that they would not have asked their general practitioner such questions [ 35 ]. These findings are supported by the results of recent surveys of Dutch women in which more than 70% of the respondents reported an interest in preconception counseling when offered by their own general practitioner [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been recommended that physicians and other health-care professionals in other clinics caring for these patients should have an easy access to diagnostic consultations. 2,14 This could optimally happen so that the clinical geneticist comes to see the patient/family, gives diagnostic suggestions and helps the physician to find recent and reliable information on the disease. Whether or not the diagnosis can, according to this advice, be ascertained, the family should be offered the possibility of genetic counseling.…”
Section: Issuesmentioning
confidence: 99%
“…Options available to couples before conception include adoption, surrogacy, use of donor sperm, pre-implantation genetic diagnosis after in-vitro fertilization, with transfer of unaffected embryos, and avoidance of pregnancy. Future technological advances will likely further broaden the choices available to couples 3, 4, 5, 6, 7…”
Section: All Individualsmentioning
confidence: 99%